(3EMcGe GdCMcGe aj CUhd GdCMcGes - (3Ydj Hf eMeO Hf SGde GdJZdHj, CHh GdMSf, Sja GdOjf GdBeOj,J (B631 (3g` s
(3ChdgG (B:s
(3GdMeO ddg NGdb GdCadGc heOjQgG hHYO aEfg deG cGfJ GMce GdTQYjI hGdbVGjG GdabgjI s
(3BNQgG (B:s
(3Edi Cf JWdY G dTeS Ch ZjQ eYdheI GdhbJ cbhdg Zdi ONhd GdOGQ ced GdLRA GdChd s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B332 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B155s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs